Financial Engineering with Copulas Explained - Mai, Jan-Frederik; Scherer, Matthias; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This is a succinct guide to the application and modelling of dependence models or copulas in the financial markets. First applied to credit risk modelling, copulas are now widely used across a range of derivatives transactions, asset pricing techniques and risk models and are a core part of the financial engineer's toolkit.
Keywords: Science; Science; Science, general